A Study To Assess The Effectiveness Of An Awareness Programme On Health Problems Among Runaway Children - Mercy Deva Priya (Indian Journal of Psychiatric Nursing)
It is estimated that a child runs away from home or care every five minutes in United Kingdom, an average of 100,00 children every year. Running away is slightly higher in girls than boys. Children are often running away from problems at home or at school. Some are dealing with very serious issues at home such as neglect, drug and alcohol addiction, their own or their parents mental health problems, violence and abuse. A few children are even forced to leave home by their parents or caretakers. Others are trying to escape common problems such as bullying, relationship difficulties, loneliness, or family breakdown. Objective: The study is to evaluate the effectiveness of awareness programme on knowledge regarding health problems among runaway children. Method: The research design for the study was Quasi experimental one group pre-test and post-test design. Simple random sampling technique was used to collect data from 60 runaway children from Bangalore Oniyavara Seva Coota shelter home. Results: The study findings revealed that the overall mean percentage in pre test is 30.93% and in post test is 90.76% in their knowledge scores as measured by improvement in mean percentage from pre test to post is 59.83%. Conclusion: The study showed that the runaway children had inadequate knowledge regarding Awareness Programme was effective in terms of gain in knowledge regarding health problems among runaway children.